2015
DOI: 10.1080/10810730.2014.977466
|View full text |Cite
|
Sign up to set email alerts
|

The Context of Collecting Family Health History: Examining Definitions of Family and Family Communication about Health among African American Women

Abstract: Public health initiatives encourage the public to discuss and record family health history (FHH) information, which can inform prevention and screening for a variety of conditions. Most research on FHH discussion and collection, however, has involved predominantly White participants and has not considered lay definitions of family or family communication patterns about health. This qualitative study of 32 African American women, 16 with a history of cancer, analyzed participants’ definitions of family, family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 39 publications
4
42
0
Order By: Relevance
“…Consistent with the literature [28][29][30], our results highlight the importance of relational factors in health communication and disease prevention. Dyads with at least one female actor are more likely to communicate about risk.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with the literature [28][29][30], our results highlight the importance of relational factors in health communication and disease prevention. Dyads with at least one female actor are more likely to communicate about risk.…”
Section: Discussionsupporting
confidence: 92%
“…In turn, interaction and information exchange in dyads can translate into shared appraisals of disease risk when they actively engage in collecting and updating their family health history. At the same time, distant and conflictual dyadic relationships can create barriers and delays in effective risk communication [30]. Prior research evaluating intervention programs on the basis of family health history has reported a number of changes associated with the provision of tailored risk feedback, including modified risk perceptions [31][32][33], more engagement in healthy behaviors [34][35][36], and increase in self-reported health communication [37,38].…”
mentioning
confidence: 99%
“…Notions of the definition of family can also differ by race/ethnicity. For example, compared to whites, African Americans consider family to extend beyond biological ties to kinship [53]. This mismatch in definition of family as affectional rather than biological may influence perceptions of who is necessary to include in FHH assessment [50-52, 54].…”
Section: Introductionmentioning
confidence: 99%
“…African Americans tend to remain silent when it comes to discussing certain family matters, particularly those that involve health [9,10]. Sometimes people are aware of their family medical history but still do not heed the risk factors or warnings.…”
Section: Introductionmentioning
confidence: 99%